Editorial Note - Terry Hutchinson (Legal Education Review)
The relationship between the quality of justice in society and the values of its (legal) practitioners is of obvious importance to the stability of society, especially in the context of professional concern with lawyers’ mixed performance in relation to major social events such as insurer collapse, tobacco litigation and asbestos compensation. We considered that lawyers' values might play some role in the decisions that are made in everyday legal practice. This paper, reporting on detailed observations of final-year Australian law students values in 2001, is part of a larger longitudinal study that explores the relationships between values and ethical behaviour for early-career legal practitioners. The study examined the effects of values systems on ethical decision-making, by situating participants within contexts that provided for ethical dilemmas. A questionnaire utilising hypothetical situations was presented in eleven scenarios. Findings of the 2001 snapshot, which were analysed using a variety of statistical tools, suggest that differing values hierarchies do significantly predict behavioural choices on ethical questions presented to participants. The implications of results are discussed in the contexts of ethics education in a tertiary educational environment and potentially, in the context of remedial education for practitioners who have been disciplined and then seek the return of a practising certificate.